Playing a musical instrument and the risk of dementia among older adults: a systematic review and meta-analysis of prospective cohort studies - Ahmed Arafa; Masayuki Teramoto; Saori Maeda; Yukie Sakai; Saya Nosaka; Qi Gao; Haruna Kawachi; Rena Kashima; Chisa Matsumoto; Yoshihiro Kokubo (figshare, 2022)
Abstract Background Engaging in leisure activities was suggested to protect older adults from dementia. However, the association between playing a musical instrument and the risk of dementia is not well-established. This study aimed to investigate this association in older adults using a systematic review and meta-analysis of prospective cohort studies. Methods Pooled hazard ratio (HR) and 95% confidence interval (CI) of having dementia for older adults playing a musical instrument were calculated using the random-effects model. We performed the I2 statistic to detect heterogeneity across studies and the test for funnel plot asymmetry to assess publication bias. The risk of bias assessment was conducted using the modified Newcastle–Ottawa Scale. Results A total of three prospective cohort studies were found eligible: two from the U.S. and one from Japan. Playing a musical instrument, in the meta-analysis, was significantly associated with a decreased risk of dementia (HR = 0.64; 95% CI: 0.41, 0.98) among older adults. No signs of significant heterogeneity across studies (I2 = 23.3% and p-heterogeneity = 0.27) or publication bias (z= -1.3 and p-publication bias = 0.18) were identified. Conclusion Playing a musical instrument was associated with a decreased risk of dementia among older adults. Older adults should be encouraged to engage in leisure activities, especially playing musical instruments.
Keywords: Medicine; Neuroscience; Developmental Biology; Science Policy; Mental Health